Incidence and risk factors of contrast-induced nephropathy after diagnostic or interventional coronary angiography - Ari, Hasan; Oztas Cosar, Selvi; Ari, Selma; Doganay, Kubra; Aydin, Cihan; Emlek, Nadir; Celiloglu, Nuran; Cetinkaya, Ahmet Seckin; Bozat, Tahsin; Melek, Mehmet (The European Research Journal, 2017)
Objectives. Contrast-induced nephropathy (CIN) is the third most common cause of acute renal failure that occurred in the hospital. In Turkey, there is not enough data about the frequency of CIN in cardiological interventions. Increased contrast volume and creatinin value are related with CIN. We also investigated the CIN predictors.Methods. A total of 2604 patients who underwent coronary angiography or percutaneous coronary intervention (PCI) in our hospital were prospectively evaluated in terms of CIN. The definition of CIN includes absolute (≥0.5mg/dl) or relative increase (≥25%) in serum creatinine at 48-72 h after exposure to a contrast agent compared to baseline serum creatinine values.Results. CIN was detected in 13.6% (355 patients) of 2604 patients. According to the procedure; CIN rate was 13.3% (280 of 2108 patients) in coronary angiography, 13.08% (50 of 382 patients) in elective PCI and 21.49% (25 of 114 patients) in primary PCI. Compared with each of these three groups patients, CIN rate was significantly higher in primary PCI group than coronary angiography (p=0.009) and elective PCI (p=0.02) groups. In multivariate analysis, age (odds ratio [OR]=1.04; 95% confidence interval [CI], 1.02-1.06; p